STUDENTS’ VIEWS ON LEARNING ENGLISH AT SMAS ISEN MULANG PALANGKA RAYA - Reyssa Aurora Carolina; Monalisa Gabriella Risanti; Debora Natalia Naibaho; Akhmad Fauzan; Tutik Haryani (JEELL (Journal of English Education, Linguistics and Literature), 2025)
English is the most commonly used international language in many parts of the world, including Indonesia. It is used in economic, social, political, artistic, scientific, and educational fields. The importance of English today is the reason why this foreign language must be taught at the school level from an early age. The government in Indonesia has also issued regulations to develop English, especially in the field of education. This study aims to find out students' views on English and the relevance of English for students' academic and career goals. The subjects of this study were 4 students from class XI of SMAS Isen Mulang Palangka Raya. Data were collected through observation and interview. The result of this study shows that students perceive that learning English is important and beneficial for them. In addition, this language also supports them in their future academic and their future careers goals.